2023
DOI: 10.1101/2023.11.14.566994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PI3Kδ activation, IL6 over-expression, and CD37 loss cause resistance to the targeting of CD37-positive lymphomas with the antibody-drug conjugate naratuximab emtansine

Alberto J. Arribas,
Eugenio Gaudio,
Sara Napoli
et al.

Abstract: PurposeThe transmembrane protein CD37 is expressed almost exclusively in lymphoid tissues, with the highest abundance in mature B cells. CD37-directed antibody- and, more recently, cellular-based approaches have shown preclinical and promising early clinical activity. Naratuximab emtansine (Debio 1562, IMGN529) is an antibodydrug conjugate (ADC) that incorporates an anti-CD37 monoclonal antibody conjugated to the maytansinoid DM1 as payload. Naratuximab emtansine has shown activity as a single agent and in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…It has already been reported that rituximab synergizes with naratuximab emtansine by increasing the endocytosis of CD37. 24 While it has been recently demonstrated that the efficacy of naratuximab emtansine relies on the expression levels of CD37, 33 our results suggest that anti-CD37 ADCs may be an option also for r/r RTX-treated patients. Interestingly, the recent work by Arribas et al , who explored the resistance mechanism to naratuximab emtansine, demonstrates that acquired resistance to this anti-CD37 ADC may lead to increased sensitivity to venetoclax.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It has already been reported that rituximab synergizes with naratuximab emtansine by increasing the endocytosis of CD37. 24 While it has been recently demonstrated that the efficacy of naratuximab emtansine relies on the expression levels of CD37, 33 our results suggest that anti-CD37 ADCs may be an option also for r/r RTX-treated patients. Interestingly, the recent work by Arribas et al , who explored the resistance mechanism to naratuximab emtansine, demonstrates that acquired resistance to this anti-CD37 ADC may lead to increased sensitivity to venetoclax.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, the recent work by Arribas et al , who explored the resistance mechanism to naratuximab emtansine, demonstrates that acquired resistance to this anti-CD37 ADC may lead to increased sensitivity to venetoclax. 33 This emphasizes the significance of examining the implications of acquired resistance to identify novel therapeutic pathways with a focus on tailored medical approaches. Finally, we show that decreased CD37 levels (up to 50% in our models) do not influence the efficacy of CD37-targeted CARs in both in vitro and in vivo settings and delineate CD37 CARs as an effective option for CD20-negative RTX-pretreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of available surface protein expression and RNA data obtained in our laboratory on the same cell lines used in this study 14,23,24 , we analyzed whether the anti-tumor activity of 177 Lulilotomab satetraxetan was affected by the expression levels of its target. 177 Lu-lilotomab satetraxetan IC50 values were negatively correlated with CD37 surface protein expression across 54 cell lines, including both B and T cell lymphoma models (r=-0.48, P=0.003) and also within the group of B-cell lymphomas (r=-0.36, P=0.015) (Figure 2A-B).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, one of the first demonstrations of the anti-tumor activity of radioimmunoconjugates in the clinical setting was with the anti-CD37 131 I MB-1 antibody given at high doses with autologous bone marrow support 11 . CD37 has also been used as the target of antibody-drug conjugates (ADCs) 6,7,[12][13][14] . Lutetium-177 ( 177 Lu) lilotomab satetraxetan (Betalutin) is a CD37-targeting radioimmunoconjugate obtained by conjugating the murine anti-CD37 IgG1 lilotomab with the bi-functional chelator p-SCNbenzyl-DOTA (satetraxetan) that chelates 177 Lu 3+ 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it controls IL-6 receptor signaling through its interaction with SOCS3. Furthermore, CD37 can mediate the aggregation of α4β1 and subsequent activation of PI3K/AKT signaling and cell survival [ 131 , 132 ]. CD63 may interact with the integrins α4β1, α3β1, α6β1, LFA-1, and β2 [ 133 ], mediating binding to the ECM (extracellular matrix) and promoting tumor cell migration.…”
Section: Interaction Between Exosomes and Recipient Cellsmentioning
confidence: 99%